National clinical practice guidelines for the treatment of symptomatic gallstone disease: 2021 recommendations from the Danish Surgical Society. (September 2022) - Shabanzadeh, Daniel Mønsted; Christensen, Dorthe Wiinholdt; Ewertsen, Caroline; Friis-Andersen, Hans; Helgstrand, Frederik; Nannestad Jørgensen, Lars; Kirkegaard-Klitbo, Anders; Larsen, Anders Christian; Ljungdalh, Jonas Sanberg; Nordblad Schmidt, Palle; Therkildsen, Rikke; Vilmann, Peter; et al.
Background and objective: Gallstones are highly prevalent, and more than 9000 cholecystectomies are performed annually in Denmark. The aim of this guideline was to improve the clinical course of patients with gallstone disease including a subgroup of high-risk patients. Outcomes included reduction of complications, readmissions, and need for additional interventions in patients with uncomplicated gallstone disease, acute cholecystitis, and common bile duct stones (CBDS). Methods: An interdisciplinary group of clinicians developed the guideline according to the GRADE methodology. Randomized controlled trials (RCTs) were primarily included. Non-RCTs were included if RCTs could not answer the clinical questions. Recommendations were strong or weak depending on effect estimates, quality of evidence, and patient preferences. Results: For patients with acute cholecystitis, acute laparoscopic cholecystectomy is recommended (16 RCTs, strong recommendation). Gallbladder drainage may be used as an interval procedure before a delayed laparoscopic cholecystectomy in patients with temporary contraindications to surgery and severe acute cholecystitis (1 RCT and 1 non-RCT, weak recommendation). High-risk patients are suggested to undergo acute laparoscopic cholecystectomy instead of drainage (1 RCT and 1 non-RCT, weak recommendation). For patients with CBDS, a one-step procedure with simultaneous laparoscopic cholecystectomy and CBDS removal by laparoscopy or endoscopy is recommended (22 RCTs, strong recommendation). In high-risk patients with CBDS, laparoscopic cholecystectomy is suggested to be included in the treatment (6 RCTs, weak recommendation). For diagnosis of CBDS, the use of magnetic resonance imaging or endoscopic ultrasound prior to surgical treatment is recommended (8 RCTs, strong recommendation). For patients with uncomplicated symptomatic gallstone disease, observation is suggested as an alternative to laparoscopic cholecystectomy (2 RCTs, weak recommendation). Conclusions: Seven recommendations, four weak and three strong, for treating patients with symptomatic gallstone disease were developed. Studies for treatment of high-risk patients are few and more are needed. Endorsement: The Danish Surgical Society.